Diagnostic Accuracy of LDBIO-Toxo II IgG and IgM Western Blot in Suspected Seroconversion in Pregnancy: A Multicentre Study - Valeria Meroni; Francesca Genco; Luigia Scudeller; Marie-Pierre Brenier-Pinchart; Hélène Fricker-Hidalgo; Coralie L’Ollivier; Luc Paris; Hervé Pelloux (Pathogens, 2022)
The high sensitivity of the automated tests used for Toxoplasma gondii serology can yield false-positive IgM results due to aspecific reactions. On the other hand, specific therapy can delay IgG production and, therefore, the diagnosis of seroconversion. There is a need for confirmation tests to early detect seroconversions during pregnancy. We conducted a multicentre study to evaluate the diagnostic accuracy of the Toxo II IgG and a new, not yet commercialised Toxo II IgM western blot (WB) (LDBio diagnostics Lyon France) on 229 sera corresponding to 93 patients with seroconversions and 158 sera corresponding to 68 patients with nonspecific IgM. Sensitivity was 97.8% for IgM WB and 98.9% for IgG WB. Specificity was 89.7% and 100%, respectively. The concordance between IgM and IgG Toxo WB with the final diagnosis was very good, K = 0.89 and K = 0.99, respectively. In 5 cases (5.4%), the appearance of IgM, and in 55 cases (59.1%), the appearance of IgG was recorded by WB earlier than by traditional tests. In 10 cases (10.8%), IgM was detected after the traditional tests and in 2 cases (2.2%) for IgG. The association of IgG and IgM WB on the same sample not only detected all seroconversions but also correctly identified most of the false-positive results.